2023
DOI: 10.1039/d2fo03775k
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of walnut-derived novel peptides against d-galactose-induced cognitive impairment by modulating the gut microbiota composition

Abstract: In our present work, RLWPF (Arg-Leu-Trp-Pro-Phe) and VLRLF (Val-Leu-Arg-Leu-Phe), were investigated the effects against D-galactose (D-gal) induced cognitive impairment via microbiota-gut-brain axis. The two novel peptides derived from walnut protein...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In addition to intervening and removing factors that induce peripheral inflammation, drugs such as ulinastatin ( Kim et al, 2023 ), α2-AR agonists Dex ( Oxlund et al, 2022 ) and guanfacine ( Arnsten et al, 2023 ), cyclooxygenase (Cox) inhibitors ( Weng et al, 2021 ), and lidocaine ( Geng et al, 2023 ) all exert anti-inflammatory or neuroprotective effects to attenuate cognitive impairment through various pathways. Peptides consisting of arginine, valine, leucine, and phenylalanine ( Li T. et al, 2023 ) and proline-rich peptides ( Banasiak-Cieslar et al, 2023 ), as well as neutralizing antibodies, such as anti-IL-17 ( Cristiano et al, 2019 ) and anti-IL-6 ( Hisaoka-Nakashima et al, 2022 ), have also been shown to have a positive effect in limiting inflammation and thus improving cognition.…”
Section: Prevention and Treatment Strategies Based On Peripheral Infl...mentioning
confidence: 99%
“…In addition to intervening and removing factors that induce peripheral inflammation, drugs such as ulinastatin ( Kim et al, 2023 ), α2-AR agonists Dex ( Oxlund et al, 2022 ) and guanfacine ( Arnsten et al, 2023 ), cyclooxygenase (Cox) inhibitors ( Weng et al, 2021 ), and lidocaine ( Geng et al, 2023 ) all exert anti-inflammatory or neuroprotective effects to attenuate cognitive impairment through various pathways. Peptides consisting of arginine, valine, leucine, and phenylalanine ( Li T. et al, 2023 ) and proline-rich peptides ( Banasiak-Cieslar et al, 2023 ), as well as neutralizing antibodies, such as anti-IL-17 ( Cristiano et al, 2019 ) and anti-IL-6 ( Hisaoka-Nakashima et al, 2022 ), have also been shown to have a positive effect in limiting inflammation and thus improving cognition.…”
Section: Prevention and Treatment Strategies Based On Peripheral Infl...mentioning
confidence: 99%
“…Various enzymes, including neutralase, alkaline protease, protamex, pepsin, trypsin, and viscozyme L, have been reported to produce peptides from walnut proteins with memory-improving properties. For instance, alkaline proteases can hydrolyse walnut protein to produce peptides (RLWPF, VLRLF) that inhibit oxidative stress and neuroinflammation, modulate the intestinal microflora and metabolites, and improve learning ability in mice [ 33 ]. Walnut-derived peptides (GGW, VYY, LLPF) can also be produced by plant hydrolase and pancreatin complexes to improve learning ability and alleviate memory loss in sleep-deprived rats [ 34 ].…”
Section: Preparation Isolation Purification and Identification Of Wal...mentioning
confidence: 99%
“…This treatment also significantly increases the activity of the AChE enzyme and reverses cholinergic dysfunction [ 22 ]. Wang et al [ 33 ] found that administering walnut protein hydrolysate orally to mice significantly improved their behavioural performance. This also helped in restoring the cholinergic system disorder and oxidative stress in the mouse brain.…”
Section: Mechanisms Of the Neuroprotective Effects Of Walnut Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 To date, several walnut peptides with neuroprotective properties have been identified, e.g., RLWPF, VLRLF, LPF, GVYY and APTLW. 15,16 Among them, RLWPF and VLRLF can regulate the intestinal flora of AD model mice, and LPF, GVYY and APTLW have been shown to alleviate neuroinflammation. Nevertheless, walnut peptides as Akt activators have not been properly investigated, and more data are still needed on walnut peptides as modulators of intestinal flora.…”
Section: Introductionmentioning
confidence: 99%